The Condition of Prospective Brides in Efforts to Have a Healthy Pregnancy to Prevent Stunting (HEALTH CARE: JURNAL KESEHATAN, 2025)
Children as a nation's next generation must be prepared before pregnancy and during pregnancy to produce a quality generation. Therefore, preconception preparation must be well prepared before undergoing the conception process. During the preconception period, it is essential for the bride and groom to pay attention to nutritional status, especially in preparing for pregnancy because it will be related to pregnancy outcomes. The purpose of this study was to analyze how the description of the condition of prospective brides in terms of knowledge, education, nutritional status, age. This type of research used descriptive-analytic. The population of this study was brides in BP4 Pekanbaru City which is 275 respondents. The results showed that the average age of the respondents was 25 years old, had a bachelor's degree (62.9%), had normal nutritional status (65.8%), and had good knowledge about stunting prevention (71.3). Based on the results of the study, it can be concluded that prospective brides at BP4 Pekanbaru City are at the ideal age for marriage, the majority have a bachelor's degree, have normal nutritional status and have good knowledge about stunting prevention. It is hoped brides will have a better understanding of stunting prevention and can make various efforts to prevent stunting in their children starting from pregnancy to the childcare process